ختان الإناث بين الموروث والمشروع - الحسن، ميادة محمد (جامعة دنقلا - كلية الدراسات العليا, 2021)
راعت الشريعة الإسلامية خمسة مصالح للإنسان هي: الدين، والنفس، والعقل، والنسل، والمال، حيث جاءت الأحكام بإيجادها وحفظها على مستوى الضرورة ثم الحاجة ثم التحسين. ومسألة (ختان الأنثى) تندرج تحت حفظ مصلحة النسل على وجه السنة والاستحباب، ومدارها على ظهور الحاجة واختلاف أعراف البلدان. وقد دار البحث حول بيان صورة الختان عند الإناث من الناحية التشريحية، ثم سرد أقوال الفقهاء وبيان أن ختان الإناث مشروع في الجملة، وأن الخلاف وقع بين الفقهاء في حكمه هل هو واجب أو سنة ومكرمة، ورجح البحث أن ختان الأنثى سنة، وهو متعلق بأعراف البلدان واحتياجات الناس فيها. والصورة المسموح بها شرعا هي: أخذ الجلدة التي تغطي البظر فقط، ولا يجوز استئصال أي جزء من البظر، أما الختان الفرعوني، وأي ختان يتم باستئصال الأعضاء التناسلية وإعادة خياطتها محرم شرعا. وإذا كان البظر لدى الأنثى ضامرا فلا يسن الختان، ولا يشرع، بل يحرم. وعلى ضوء البحث جاءت التوصية بأن ينظم ولاة الأمر في البلدان التي تتوارث فيها عادة ختان الأنثى عملية الختان، فلا يسمح بإجرائها إلا على يد المختصين من الأطباء ومن في حكمهم وفي بيئة معقمة نظيفة بحيث لا تتعرض المختونة للضرر.
The Islamic law always considers five interests for human beings in all its laws, which are: religion, life, mind, reproduction (generation) and finance furthermore, it tries to consider and protect them under the light of necessity then needs then improvement at the best. This research puts the issue of “female circumcision”, which is one of the concepts that goes under the reproduction interest protection, under the spot due to the arising need and the cultural differences. In this research, female circumcision was explained first from anatomical point of view then jurists' opinions where listed to clarify that female circumcision is allowed in agreement and the disagreement came from that is it a must or only recommended?. The researcher concluded that female circumcision is recommended and it depends on cultures and its people needs. In addition, female circumcision must be done ,under Islamic law, by excising only the skin overlying the clitoris thus, excising any genitalia including the clitoris and reshaping it, which is called “pharaonic circumcision”, is forbidden. Furthermore, the researcher recommends that female circumcision, in allowed cultures and countries, must be regulated by the government as to be done by specialized surgeons under aseptic techniques to avoid any adverse effects.
Keywords: ختان الإناث -- حفظ النسل -- الأحكام الشرعية -- الشريعة الإسلامية -- العادات والتقاليد